Evolutionary Patterns of Thylakoid Architecture in Cyanobacteria - Mareš, Jan; Strunecký, Otakar; Bučinská, Lenka; Wiedermannová, Jana (Frontiers in microbiology, 2019)
While photosynthetic processes have become increasingly understood in cyanobacterial model strains, differences in the spatial distribution of thylakoid membranes among various lineages have been largely unexplored. Cyanobacterial cells exhibit an intriguing diversity in thylakoid arrangements, ranging from simple parietal to radial, coiled, parallel, and special types. Although metabolic background of their variability remains unknown, it has been suggested that thylakoid patterns are stable in certain phylogenetic clades. For decades, thylakoid arrangements have been used in cyanobacterial classification as one of the crucial characters for definition of taxa. The last comprehensive study addressing their evolutionary history in cyanobacteria was published 15 years ago. Since then both DNA sequence and electron microscopy data have grown rapidly. In the current study, we map ultrastructural data of >200 strains onto the SSU rRNA gene tree, and the resulting phylogeny is compared to a phylogenomic tree. Changes in thylakoid architecture in general follow the phylogeny of housekeeping loci. Parietal arrangement is resolved as the original thylakoid organization, evolving into complex arrangement in the most derived group of heterocytous cyanobacteria. Cyanobacteria occupying intermediate phylogenetic positions (greater filamentous, coccoid, and baeocytous types) exhibit fascicular, radial, and parallel arrangements, partly tracing the reconstructed course of phylogenetic branching. Contrary to previous studies, taxonomic value of thylakoid morphology seems very limited. Only special cases such as thylakoid absence or the parallel arrangement could be used as taxonomically informative apomorphies. The phylogenetic trees provide evidence of both paraphyly and reversion from more derived architectures in the simple parietal thylakoid pattern. Repeated convergent evolution is suggested for the radial and fascicular architectures. Moreover, thylakoid arrangement is constrained by cell size, excluding the occurrence of complex architectures in cyanobacteria smaller than 2 μm in width. It may further be dependent on unknown (eco)physiological factors as suggested by recurrence of the radial type in unrelated but morphologically similar cyanobacteria, and occurrence of special features throughout the phylogeny. No straightforward phylogenetic congruences have been found between proteins involved in photosynthesis and thylakoid formation, and the thylakoid patterns. Remarkably, several postulated thylakoid biogenesis factors are partly or completely missing in cyanobacteria, challenging their proposed essential roles.
Keywords: taxonomy; thylakoid pattern; cyanobacteria; SSU rRNA gene; phylogenomics; evolution; photosynthesis